PALAEONTOLOGICAL (RADIOLARIAN) LATE JURASSIC AGE CONSTRAINT FOR THE STEPANAVAN OPHIOLITE (LESSER CAUCASUS, ARMENIA) - Danelian, T.; Galoyan, G.; Rolland, Y.; Sosson, M. (Bulletin of the Geological Society of Greece, 2007)
Micropalaeontological age evidence for the sedimentary cover of ophiolites is important to understand the palaeogeographic and geodynamic evolution of Tethyan realms. The Stepanavan ophiolitic suite of Northern Armenia consists of peridotites, gabbros, plagiogranite and lavas with a radiolarite sedimentary cover. It is regarded as the northern extension of the Sevan Akera ophiolitic zone and may be considered as the eastern extension of the Izmir-Ankara suture zone. It represents the relics of a slow-spreading mid oceanic ridge that was active between Eurasia and the South-Armenian Block of Gondwanian origin. Radiolaria extracted from radiolarites of the Stepanavan ophiolite provide for the first time a Late Jurassic (late Kimmeridgian to early Tithonian) age constraint for this part of Tethyan oceanic crust preserved in Lesser Caucasus.